LEGAL ISSUES OF CORRELATION BETWEEN STATE AND PUBLIC CONTROL IN THE SPHERE OF HIGHER EDUCATION - A. Y. Aleksandrov; S. B. Vereshchak; O. A. Ivanova (Russian Journal of Economics and Law)
Objective: to determine the ratio of different types of state and public control in the sphere of higher education and to propose an optimal model of their interaction. Methods: systemic-structural approach to the analysis of the research object, comparative-legal and logical methods. Results: basing on the regulatory framework analysis, licensing procedures, state and public accreditation of basic educational programs in the field of higher education, critical consideration of the main directions of state policy in the sphere of education, the authors summarize the educational reform, make proposals on improving the legal tools in the sphere of higher education control and supervision in the Russian Federation. Scientific novelty: for the first time, the different parameters of the state and public control in the sphere of higher education were comprehensively examined in the context of compliance with the principles of state management. Practical value: basing on the study of the theoretical foundations and practical examples, the authors make proposals to improve the existing legislation regulating relations in the sphere of state and public control of higher education.